2019
DOI: 10.1096/fasebj.2019.33.1_supplement.351.4
|View full text |Cite
|
Sign up to set email alerts
|

Can Cellular Labile Iron Pool be Considered Solely a Pro‐oxidant Species in Cells?

Abstract: The ubiquitous cellular labile iron pool (LIP) is often associated with the production of the highly reactive species hydroxyl radical, which forms through redox reaction with hydrogen peroxide. Several studies indicate that LIP‐dependent hydroxyl radical production causes cellular damage through oxidation of biomolecules. Although LIP's interaction with hydrogen peroxide and its effects are well established, the interaction of LIP and peroxynitrite, and it's effects are not yet understood. Does peroxynitrite,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It was suggested that LIP intercepts ONOO − and its free radical derivatives, e.g., • NO 2 and • CO 3 [60]. The antioxidant effect of bivalent iron for peroxynitrite is explained by its ability to reduce ONOO − to nitrite by two-electron mechanism, with a rate constant being two orders higher than that of ONOO − reaction with CO 2 [58,61].…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that LIP intercepts ONOO − and its free radical derivatives, e.g., • NO 2 and • CO 3 [60]. The antioxidant effect of bivalent iron for peroxynitrite is explained by its ability to reduce ONOO − to nitrite by two-electron mechanism, with a rate constant being two orders higher than that of ONOO − reaction with CO 2 [58,61].…”
Section: Discussionmentioning
confidence: 99%